Correlation of lymph node size and their metastatic infiltration in gastric adenocarcinoma - Deb, Pratap Kumar; Fazal, Syed Abul (International Surgery Journal, 2020)
Background: In adenocarcinoma stomach, lymph node involvement is a significant predictor of survival, and a decisive factor in planning management. Size has always been an important criterion while considering the metastatic status of the node, in its radiological evaluation or otherwise. However, to what extent the size of a node can be considered as a reliable criterion for its metastatic potential remains a question. Methods: The present study is based on retrieving lymph nodes per operatively from patients of carcinoma stomach, measuring each node, evaluating its metastatic status and comparing the results to find a correlation between these two parameters. Results: The present study, examined a total of 187 nodes from 30 gastrectomy specimens. Among them, metastasis was found in 59 nodes (31.55%). Among these metastatic nodes, 34 (57.62%) were actually less than 5mm in size. Among the total sizes of all the lymph nodes examined, the mean±SD (standard deviation) of the metastasis positive nodes were found to be 6.42±3.86 mm, while that of the non-metastatic nodes were found to be 5.51±1.99 mm. However, it was also observed that larger nodes (>1 cm), tend to have a high chance of being malignant (62.5%). Conclusions: The above study shows though large nodes tend to be malignant, ignoring small nodes can lead to gross under staging or incomplete clearance while treating patients of adenocarcinoma stomach. Smaller nodes constitute a significant proportion of malignant nodes and must be evaluated. Size is not a reliable criterion of metastasis in lymph nodes of carcinoma stomach.